Life as art : aesthetics and the creation of self - Simpson, Zachary, 1979- (Lexington Books, 2012)
Life as Art synthesizes a number of aesthetic theories in philosophy after 1850 and shows the ways in which they contribute to a unified field of analysis and potential implementation. The book is framed both as a secondary text, analyzing 19th and 20th Century aesthetics, and a primary argument for the viability of life as art as a unified philosophical position.